2012
DOI: 10.1093/cvr/cvs371
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diabetes-induced arginase activation and vascular dysfunction by Rho kinase (ROCK) knockout

Abstract: Partial deletion of either ROCK isoform, but to a greater extent ROCK1, attenuates diabetes-induced vascular endothelial dysfunction by preventing increased arginase activity and expression and reduction in NO production in type 1 diabetes. Limiting ROCK and arginase activity improves vascular function in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 45 publications
8
70
0
2
Order By: Relevance
“…[51][52][53][54] Several reports demonstrated that NO and Rho-kinase have opposing effects. 55,56 Rho-kinase-deficient mice revealed preserved EC function in a diabetic model. 56 Moreover, a Rho-kinase inhibitor, fasudil, significantly enhanced the 57,58 Statins upregulate eNOS by cholesterolindependent mechanisms, involving the inhibition of Rho geranyl-geranylation.…”
Section: Opposing Effects Of No and Rho-kinase In Ec Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…[51][52][53][54] Several reports demonstrated that NO and Rho-kinase have opposing effects. 55,56 Rho-kinase-deficient mice revealed preserved EC function in a diabetic model. 56 Moreover, a Rho-kinase inhibitor, fasudil, significantly enhanced the 57,58 Statins upregulate eNOS by cholesterolindependent mechanisms, involving the inhibition of Rho geranyl-geranylation.…”
Section: Opposing Effects Of No and Rho-kinase In Ec Functionmentioning
confidence: 97%
“…55,56 Rho-kinase-deficient mice revealed preserved EC function in a diabetic model. 56 Moreover, a Rho-kinase inhibitor, fasudil, significantly enhanced the 57,58 Statins upregulate eNOS by cholesterolindependent mechanisms, involving the inhibition of Rho geranyl-geranylation. 59 In addition, small GTP-binding protein dissociation stimulator plays a central role in the pleiotropic effects of statins, independently of the Rho-kinase pathway.…”
Section: Opposing Effects Of No and Rho-kinase In Ec Functionmentioning
confidence: 97%
“…Accordingly, arginase blockade results in improved endothelial function. 7,[11][12][13] This mechanism also seems to be highly relevant for patients with cardiovascular disease. We have shown that arginase blockade markedly improves endothelium-dependent vasodilatation in patient with coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…827 828 829 830 831 832 833 834 835 836 837 838 839 840 841 842 843 844 845 846 847 848 849 850 851 852 853 854 855 856 857 858 859 860 861 862 863 864 865 866 867 868 869 870 871 872 873 874 875 876 877 878 879 880 881 882 883 884 885 Elevated levels of peroxynitrites have been recently associated to an increased RhoA activity, largely responsible for vascular dysfunction in experimental diabetes [231]. On the same line, diabetesinduced endothelial aortic dysfunction is improved in ROCK knockout mice [232]. ROCK inhibitors such as Y-27632 and fasudil have shown promising therapeutic advantages on cardiovascular diseases including atherosclerosis, pulmonary and systemic hypertension and chronic heart failure [233,234], as well as significant beneficial effects on diabetic endothelial dysfunction of retinal [235], coronary [236] and intrarenal arteries [237].…”
Section: Rock (Rho-associated Kinase) Inhibitors -mentioning
confidence: 99%